Qualitative analysis of the alternative learning system : basis for policy review - Agbayani, Leonila C. (Laoag City : [s.n.], 2019)
The study is a qualitative analysis of different components of the Alternative Learning System (ALS) of the Department of Education as the basis for the identification of pointers for possible policy review. ALS graduates were classified on the basis of their self-perceived success, or lack of it, and the reasons for their perceptions were identified. Described were the characteristics (academic and motivational) of the graduates and the instructional competencies (attitudes, instructional behaviors: key and helping behaviors) of the implementers, the learning environment (physical, psychological, instructional materials), and the graduates' support system (family, peers, school administrators and local government units). From the descriptions, the factors which the graduates and implementers attribute the former's self-perceived success or lack of it, as well as the factors that could contribute to the successful implementation of a non-formal education program, were logically identified.
Bibliography: pages 142-144.
CHED-La Union
Keywords: Educational test and measurements; Alternative learning system